Coulomb stressing rate changes and seismicity dynamics associated with slow slip events in south-central Alaska - ShanShan Li; XingLei Li; Bing Xu (Earth and Planetary Physics)
Two long-term slow slip events (SSEs) in Lower Cook Inlet, Alaska, were identified by Li SS et al. (2016). The earlier SSE lasted at least 9 years with Mw ~7.8 and had an average slip rate of ~82 mm/year. The latter SSE, occurring in a similar area, lasted approximately 2 years with Mw ~7.2 and an average slip rate of ~91 mm/year. To test whether these SSEs triggered earthquakes near the slow slip area, we calculated the Coulomb stressing rate changes on receiver faults by using two fault geometry definitions: nodal planes of focal mechanism solutions of past earthquakes, and optimally oriented fault planes. Regions in the shallow slab (30–60 km) that experienced a significant increase in the Coulomb stressing rate due to slip by the SSEs showed an increase in seismicity rates during SSE periods. No correlation was found in the volumes that underwent a significant increase in the Coulomb stressing rate during the SSE within the crust and the intermediate slab. We modeled variations in seismicity rates by using a combination of the Coulomb stress transfer model and the framework of rate-and-state friction. Our model indicated that the SSEs increased the Coulomb stress changes on adjacent faults, thereby increasing the seismicity rates even though the ratio of the SSE stressing rate to the background stressing rate was small. Each long-term SSE in Alaska brought the megathrust updip of the SSE areas closer to failure by up to 0.1–0.15 MPa. The volumes of significant Coulomb stress changes caused by the Upper and Lower Cook Inlet SSEs did not overlap.